2022
DOI: 10.1051/parasite/2022047
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous leishmaniasis in Iran: A review of epidemiological aspects, with emphasis on molecular findings

Abstract: Leishmania parasites can cause zoonotic cutaneous leishmaniasis (CL) by circulating between humans, rodents, and sandflies in Iran. In this study, published data were collected from scientific sources such as Web of Science, Scopus, PubMed, Springer, ResearchGate, Wiley Online, Ovid, Ebsco, Cochrane Library, Google scholar, and SID. Keywords searched in the articles, theses, and abstracts from 1983 to 2021 were cutaneous leishmaniasis, epidemiology, reservoir, vector, climatic factors, identification, and Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Furthermore, the important centers in Isfahan are Barkhar, Mimeh, Ardestan, Natanz, Aran-Bidgol, and Kashan (27,28). Studies in the field of human leishmaniasis revealed that INF-γ and IL12 (Th1 profile) play a determining role in protecting against the disease and IL-4 and IL-10 (Th2 profile) in maintaining the disease (29,30). When anti-ESA is present in the environment, the average level of IL-4 secretion in PBMCs cultured with different Leishmania antigens exhibits the lowest amount of this cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the important centers in Isfahan are Barkhar, Mimeh, Ardestan, Natanz, Aran-Bidgol, and Kashan (27,28). Studies in the field of human leishmaniasis revealed that INF-γ and IL12 (Th1 profile) play a determining role in protecting against the disease and IL-4 and IL-10 (Th2 profile) in maintaining the disease (29,30). When anti-ESA is present in the environment, the average level of IL-4 secretion in PBMCs cultured with different Leishmania antigens exhibits the lowest amount of this cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of leishmaniasis in the Old World is mostly in the Middle East. Furthermore, cutaneous leishmaniasis has a high prevalence in 12 countries, Algeria, Colombia, Brazil, Iran, Syria, Peru, Morocco, Tunisia, Afghanistan, Pakistan, Turkey, and Saudi Arabia (2). Cutaneous leishmaniasis cases are currently common in many rural areas of 19 out of 31 provinces of Iran (3,4).…”
Section: Introductionmentioning
confidence: 99%